2008
DOI: 10.1016/j.ypmed.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Is provider training effective? Changes in attitudes towards smoking cessation counseling and counseling behaviors of home health care nurses

Abstract: Objective-We prospectively examined whether training home health care nurses is associated with changes in attitudes towards smoking cessation counseling and counseling behaviors.Methods-We trained 98 home health care nurses to deliver cessation counseling to their patients. Measures were administered at pre-training, post-training, and six months later. This was part of a larger study conducted in Providence, RI, USA (1998-2002.Results-Compared with pre-training, at post-training, nurses reported significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 17 publications
2
54
1
5
Order By: Relevance
“…41 Studies show that training on the 5A’s as well as training in appropriate communication skills and patient-centered counseling methods such as motivational interviewing can improve smoking cessation. 42 Thus, providing training, tools and resources on how to effectively implement the 5A’s are needed. In addition, healthcare systems changes such as provider reminders and including the 5A’s in electronic medical records may help to facilitate delivery of these interventions and integration into routine prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…41 Studies show that training on the 5A’s as well as training in appropriate communication skills and patient-centered counseling methods such as motivational interviewing can improve smoking cessation. 42 Thus, providing training, tools and resources on how to effectively implement the 5A’s are needed. In addition, healthcare systems changes such as provider reminders and including the 5A’s in electronic medical records may help to facilitate delivery of these interventions and integration into routine prenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established that doctors with healthy behaviors and adequate knowledge of preventive medicine are more motivated to work with their patients in this area and that their interventions are more credible and effective than those without healthy behaviors and adequate knowledge [14][15][16][17][18][19]. Therefore, emphasizing these aspects during medical training reduces the burden of non-communicable diseases [14][15][16][17][18][19][20][21]. Our study provides useful information on the factors associated with unhealthy practices and their relationship with preventive counseling attitudes in a developing country, where both the influence of tobacco companies and unhealthy behaviors are on the rise.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that health professionals who have received training in preventive medicine tend to have healthier lifestyles and better attitudes toward preventive counseling [14,15]. Furthermore, studies have observed that counseling has a higher level of impact and effectiveness if the provider is a model of the messages transmitted to the patients [2,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO recommends that all health professionals be trained to advise and help smokers stop smoking, and that education and training start at the undergraduate level and continue on through clinical training (WHO, 2001;WHO, 2003). Evidence from a range of health professional training programmes suggests that relatively brief training can have an impact (Borelli et al, 2008;Sheffer et al, 2009;Maynard et al, 2012). To provide further training for health professionals such as psychologists following the completion of formal university education, it may be important to explore flexible forms of delivery, such as tele-health, videoconferencing and on-line formats (Mitchell et al, 2008;Maynard et al, 2012).…”
Section: Discussionmentioning
confidence: 99%